"I don't remember any of us … having diabetes or cancer": How historical oppression undermines Indigenous foodways, health, and wellness. Issue 1 (2nd January 2023) - McKinley, Catherine E.; Jernigan, Valarie Blue Bird
Abstract: Past and present structures of settler colonial historical oppression aimed to erase and replace Indigenous peoples have profoundly disrupted U.S. Indigenous foodways. The purpose of this article is to use the Indigenous Framework of Historical Oppression, Resilience, and Transcendence (FHORT) to understand U.S. Indigenous peoples' experiences and perceptions of how (a) foodways have changed within the context of settler colonial historical oppression and (b) these changes have affected wellness and cultures of Indigenous peoples. Critical ethnographic analysis focused on data from 31 interviews with participants from a rural Southeast reservation and a Northwest urban context. Results revealed participants' descriptions of changing foodways situated in a system of historical oppression, with themes including (a) historical oppression and changing values and foodway practices; (b) settler colonial governmental programs interrupting foodways through commodities and rations; and (c) changing foodway practices: from homegrown and homemade to fast food and premade. Participants described the aftermath of settler colonial governmental policies and programs undermined foodways, connectedness, cultural knowledge, family and interpersonal relationships, ceremonies, and outdoor activities—all of which promote health and wellness. To redress historical oppression, including settler colonial governmental policies, decolonized decision-making, foodways, and Indigenous food sovereignty are recommended as approaches to inform policy and programming that affirms Indigenous values and worldviews.